Acceptance and transfer to a regional severe respiratory failure and veno‐venous extracorporeal membrane oxygenation (ECMO) service: predictors and outcomes12. (23rd November 2017) - Gillon, S. A.; Rowland, K.; Shankar‐Hari, M.; Camporota, L.; Glover, G. W.; Wyncoll, D. L. A.; Barrett, N. A.; Ioannou, N.; Meadows, C. I. S.
Summary: The use of extracorporeal membrane oxygenation for respiratory failure is high risk and resource intensive. In England, five centres provide this service and patients who are referred have four possible outcomes: declined transfer due to perceived futility; accepted in principle but remain at the referring centre with ongoing surveillance; retrieved using conventional ventilation; or retrieved on extracorporeal support. The decision‐making process leading to these outcomes has not previously been examined. We evaluated referrals to one centre and identified factors associated with each decision outcome. Five hundred and sixty‐four patients were analysed from January 2012 to October 2015. One hundred and fifty‐seven patients were declined; multivariate analysis demonstrated associated factors to be: age (odds ratio (95% confidence interval) 1.05 (1.04–1.07)); immunocompromise (4.95 (2.58–9.67)); lactate (1.11 (1.01–1.22)); duration of ventilation (1.08 (1.04–1.14)); and cardiac failure (3.22 (1.04–10.51)). Factors associated with the decision to retrieve an accepted patient were: plateau pressure (1.05 (1.01–1.10)); ratio of arterial oxygen partial pressure to fractional inspired oxygen (0.89 (0.85–0.93)); partial pressure of carbon dioxide in arterial blood (1.13 (1.03–1.25)); and the absence of non‐pulmonary infection (0.31 (0.15–0.61)). Only pH was independently associated with the decision to transfer on extracorporeal support (0.020 (0.002–0.017)). Six‐month survival in the declined, non‐retrieved, conventionally retrieved and extracorporeal‐retrieved groups was 16.6%, 71.1%, 76.7% and 72.1%, respectively, substantially supporting the decision‐making model. Survival in the accepted group exceeds that reported previously. However, a proportion of those declined do survive and some remotely managed patients die. This suggests the approach does not account for some important survival‐determining factors.